SELECTION AND PREPARATION OF ATHLETES FOR SPORTS - Bokhodirjon Yursinboyevich Khaydarov (American Journals Publishing, 2022)
This article talks about achieving the best results in sports through proper selection and orientation to the most suitable sports in terms of body structure and composition as the first stage of training athletes.
Keywords: physical education classes, morphological, biomechanical, psychological indicators